INTEGRATION OF CIRCULAR ECONOMY AND DIGITAL TECHNOLOGIES IN THE OIL AND GAS SECTOR (American Journal of Business Management, Economics and Banking, 2025)
The circular economy is considered as a model of an economic system that is able, on the one hand, to respond to the challenges facing society, and on the other hand, to ensure a sufficiently high efficiency of the activities of economic entities. In practice, the process of transition to a circular economy is rather slow. The article analyzes the integration of the circular economy and digital technologies as drivers for the creation of closed production cycles.